Toward sustainability: a conceptual framework for South African social enterprises - Armstrong, Ridge McGibbon (Stellenbosch : Stellenbosch University, 2025)
Armstrong, R. M. 2025. Toward Sustainability: A Conceptual Framework for South African Social Enterprises. Unpublished doctoral dissertation. Stellenbosch: Stellenbosch University [online]. Available: https://scholar.sun.ac.za/items/657d961d-22d4-4b7d-93ae-e234f0598f69